2019
DOI: 10.1002/adts.201900146
|View full text |Cite
|
Sign up to set email alerts
|

On the Crack‐Tip Region Stress Field in Molecular Systems: The Case of Ideal Brittle Fracture

Abstract: Continuum-based fracture mechanics breaks down at the nanoscale where the discrete nature of atoms cannot be neglected. Intriguingly, this work shows that the concept of stress intensity factor is still valid if the atoms are modeled. Molecular statistics simulations are conducted on single-edge cracked samples of ideal brittle silicon, varying the size until few nanometers. The local virial stress, derived as the functional derivative of the free energy of a molecular system with respect to the deformation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The FFM, as introduced earlier, is a coupled criterion, i.e., it requires two conditions to be full-filled, one based on stress and the other on energy considerations. The stress criterion could be developed by considering the virial stress, provided that it is accepted as a representation of the mechanical stress at the atomic scale as recently showed in [20], or by employing a traction vector-based stress recently proposed in [54]. The energy criterion, instead, could be defined based on interatomic potential energy as provided in some recent examples based on the energy release rate [22,23] and on the averaged strain energy density [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFM, as introduced earlier, is a coupled criterion, i.e., it requires two conditions to be full-filled, one based on stress and the other on energy considerations. The stress criterion could be developed by considering the virial stress, provided that it is accepted as a representation of the mechanical stress at the atomic scale as recently showed in [20], or by employing a traction vector-based stress recently proposed in [54]. The energy criterion, instead, could be defined based on interatomic potential energy as provided in some recent examples based on the energy release rate [22,23] and on the averaged strain energy density [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently quantified the small scale breakdown of continuum-based linear elastic fracture mechanics (LEFM) and have demonstrated that continuum-based methods are still valid at small scale if that limit is not reached [15][16][17][18]. The breakdown was expressed in terms of the ratio between the crack singular stress field length, which surprisingly is still characterizing the crack at a very small scale [19][20][21], and the fracture process zone. When this ratio is in the order of 4-5, continuum-based LEFM breaks down and the discrete nature of atoms cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fracture tests by means of MS simulations were conducted by using opensource code LAMMPS [24]. While details can be found in [23], important aspects are presented hereafter. The modified Stillinger-Weber (SW) interatomic potential [25] was employed.…”
Section: Review Of Recent Molecular Statistics Simulations On Crackedmentioning
confidence: 99%
“…Setting aside the debate on the validity of the virial stress as a representation of mechanical stress at atomic scale, in the present work the focus is on the applicability of classic continuum concepts in the presence of defects, such as the stress intensity factor (SIF). By reviewing recent molecular statistics (MS) analyses on single-edged cracked samples loaded under mode I [23], and representative of ideal brittle fracture, it is demonstrated that the virial stress shows the trend of inverse square root singularity and that computation of the SIF according to Irwin's concept is possible. Furthermore, the breakdown of continuum linear elastic fracture mechanics, recently defined by means of energy concepts [11][12][13], is here quantified by using merely the stress fields.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, different types of materials have been the focus of micromechanical investigations on fatigue crack initiation in the absence of NMI. Selected works are for example: On polycrystalline ferritic and ferritic-pearlitic steels [24][25][26], on martensitic steels [27][28][29], on aluminum alloys [30], on nickel-base alloys [18,23,31,32] and finally on ideal brittle materials [33,34]. The listed works are exemplary and there is no claim to completeness.…”
Section: Introductionmentioning
confidence: 99%